1997
DOI: 10.1021/ja964406g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Homogeneous Catalysis and the “3,5-Dialkyl Meta-Effect”. MeO−BIPHEP Complexes Related to Heck, Allylic Alkylation, and Hydrogenation Chemistry

Abstract: The enantioselectivities arising from a Pd-catalyzed Heck reaction (>98% ee) and an allylic alkylation (>90% ee) using a 3,5-di-tert-butyl-MeO−BIPHEP chiral auxiliary (1) are reported. Higher ee's are observed with the 3,5-dialkyl substituents than with the unsubstituted parent MeO−BIPHEP. It is proposed that the observed dialkyl “meta-effect”, on enantioselectivity, is the combined result of a more rigid and slightly larger chiral pocket and that this effect will have some generality in homogeneous catalysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
51
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 44 publications
13
51
0
2
Order By: Relevance
“…This is supported by the solid state structures of the gold complexes 8 and 12. Multiple 3,5-bis-substitution of so-called BIPHEP (2,2-bis(diarylphosphanyl)biphenyl) ligands leading to a Ômeta-effectÕ in catalysis was reported by Pregosin et al [13]. In that case the meta-substitution pattern resulted in the formation of a more rigid and slightly larger chiral pocket in the corresponding Ru-complex.…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by the solid state structures of the gold complexes 8 and 12. Multiple 3,5-bis-substitution of so-called BIPHEP (2,2-bis(diarylphosphanyl)biphenyl) ligands leading to a Ômeta-effectÕ in catalysis was reported by Pregosin et al [13]. In that case the meta-substitution pattern resulted in the formation of a more rigid and slightly larger chiral pocket in the corresponding Ru-complex.…”
Section: Discussionmentioning
confidence: 93%
“…[67,68] Pregosin and co-workers studied the Pd-catalyzed enantioselective intermolecular Heck reaction using ligands 74 and 75. [69] The enantioselection of 75 with bis(3,5-tert-butylphenyl) substituents at the phosphorus atom proved superior to 74, which has a diphenylphosphanyl group. For example, the transfer of a phenyl group to 2,3-dihydrofuran (55) to give 57 (with Ar Ph) occurred regioselectively with 75, and afforded the product with excellent enantiomeric excess (b 98 %) and in 65 % yield.…”
Section: : Ar = Phmentioning
confidence: 99%
“…The absolute values of the calculated barriers were off by more than (5 kcal/mol À1 ) in some cases. Pregosin's group attempted to use molecular mechanic (MM+) calculations to predict the rotational barriers of biaryl phosphine ligands with slightly less reliable relative prediction (Trabesinger et al, 1997). They also found that the absolute values of the calculated barriers were far removed from the experimentally determined values.…”
Section: Introductionmentioning
confidence: 99%